Android-Based Learning Multimedia E-Module Flip-Book Design - ., Elisa; ., Darwis; Mulyani Pohan, Heni; F D Harahap, A (KnE Social Sciences, 2023)
In fact, the teaching materials are still using teaching books, so in the learning media courses will be developed based on digital art teaching materials at Universitas Muhammadiyah Tapanuli Selatan. In the development of the teaching materials contain teaching materials tailored to the curriculum that applies with the tools and materials contained in the environment. Research objectives to know the expert opinion on the feasibility test and influence of the development of digital art-based teaching materials. Research and Development (R&D) method of ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). For the average result of expert validator assessments on this study covers aspects of feasibility standards based on BSNP by 3.27, then the validity criteria is quite good {quite valid and need revision}. The result of student learning creativity Assessment was obtained at 3.18, hence the creativity category is creative. Keywords: Flip-Book design; multimedia; Android-based; ADDIE